Implementasi Vigenere Cipher dalam Mengenkripsi Pesan - Raden Aris Sugianto; Wulan Dari; Dian Maya Sari; Anton Purnama (STIKes Ibnu Sina Ajibarang, 2024)
Messages require high security in the exchange process because the message is confidential and may only be read by the intended recipient. Information security problems in messages are often encountered, such as active eavesdropping, passive eavesdropping, fraud and data manipulation by unauthorized parties. To overcome this problem, cryptography can be used. This research uses cryptographic techniques with the Vigenere Cipher method to encrypt messages. The aim of this research is to encrypt messages to produce codes that will be sent to the recipient. The encryption process is carried out using the Vigenere Cipher method in the Python programming language. The researcher implemented a program to encrypt the message. The research results show that messages can be protected more strongly and securely. So, if the message is hijacked or intercepted by irresponsible parties, it will be difficult for them to find out the contents of the message. In this way, the confidentiality and authenticity of the message is maintained until it reaches the recipient.